Effect of superabsorbent polymers (SAPs) on rheological properties of fresh cement-based mortars — Development of yield stress and plastic viscosity over time. (January 2015) - Mechtcherine, Viktor; Secrieru, Egor; Schröfl, Christof
Abstract: Superabsorbent polymers (SAPs) are a new, promising, multipurpose chemical admixture for concrete. This article addresses the rheological behaviour of fresh, cement-based mortars modified with SAP. Two types of SAP with differing water absorption and desorption kinetics were used. Additionally, for one the grading was varied. Three reference mortars were investigated. The rheological properties of these fresh mortars were tested for 90 min by continuous flow rheometry. It was found that the distinct kinetics of water uptake inherent in the SAP samples, as governed by their particular chemical structures, is the major factor that governs the rheological properties of fresh mortar. Furthermore, the grading of SAP distinctly affects the development of yield stress and plastic viscosity over time. The particular effects of specific SAP addition on the rheological characteristics of a mortar depend on the water-to-binder ratio, the dosage of superplasticizer, and the dosage of silica fume, if present.